TRANSFORMING HEALTH BEHAVIOR THROUGH FAMILY ENGAGEMENT: A LITERATURE REVIEW ON STUNTING PREVENTION STRATEGIES - Sutrisnawati; Masruroh; Armada, Ade; Nasrudin (Universitas Nahdlatul Ulama Surabaya, 2025)
Introduction: Stunting remains a significant public health issue in low- and middle-income countries, including Indonesia, with long-term impacts on child development and national productivity. Family engagement has emerged as a critical factor in transforming maternal health behaviors to prevent stunting. Objective: This integrative review aimed to explore the role of family engagement in promoting behavioral change and maternal motivation for stunting prevention, and to identify evidence-based strategies supported by relevant theoretical frameworks. Design: An integrative review approach was employed to synthesize findings from diverse study designs (quantitative, qualitative, and mixed-methods) following the five-stage framework of Whittemore and Knafl (2005). Data Sources: Relevant literature covering the period from 2018 to 2024 was retrieved from PubMed, Scopus, CINAHL, Google Scholar, and ScienceDirect. Review Methods: A total of 248 records were initially identified. After applying inclusion and exclusion criteria and quality appraisal using the MMAT 2018, 21 studies were included in the final synthesis. Thematic analysis categorized findings based on behavioral outcomes, intervention types, and contextual factors. Results: Four key domains emerged from the synthesis: (1) enhancement of maternal motivation and self-efficacy through family involvement; (2) knowledge transfer via inclusive health education; (3) emotional and social support mechanisms; and (4) culturally adapted interventions. Theoretical models such as the Health Belief Model, Self-Determination Theory, and Theory of Planned Behavior helped explain the motivational processes underlying behavior change. Conclusions: Family engagement strategies are essential in transforming maternal behaviors and preventing stunting. Effective interventions should be context-specific, theory-driven, and inclusive of family and community dynamics. These findings provide valuable insights for designing sustainable, family-centered public health programs.